PENGARUH PERCEIVED ENVIRONMENTAL KNOWLEDGE DAN ENVIRONMENTAL CONCERN TERHADAP NIAT KUNJUNGAN PELANGGAN DI HOTEL MERCURE GRAND MIRAMA SURABAYA - Mubarak, Arya; Rahayu, Siti; Widjaja , Fitri Novika (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
Abstrak : This study aims to analyze the effect of perceived green knowledge and environmental concern on customers' intention to visit eco-friendly hotels, with a focus on Hotel Mercure Grand Mirama Surabaya. The findings show that environmental knowledge significantly influences customers' intention to stay at hotels that implement eco-friendly practices. Additionally, environmental concern also impacts the intention to visit green hotels. Green trust plays a mediating role in these relationships. This study provides recommendations for the hospitality industry to enhance their image as an eco-friendly hotel by educating customers and being transparent about the sustainability practices implemented. Keyword : Perceived Green Knowledge, Environmental Concern, Green Trust, Green Hotel Visit Intention, Sustainable Tourism.